Design Principles and Concept Research in “Interior Architecture Design Studio I” During the Pandemic Period - Kasap, Handan Özsırkıntı; ALTIN, ELİF; Erhene, Ayşe İpek (Nilay ÖZSAVAŞ ULUÇAY, 2022)
This research was conducted during Covid 19 Pandemic -when University Education was provided online- as a part of the Design Studio I course for the first-year students of the Interior Architecture Department of Maltepe University, Faculty of Architecture, and Design in the 2020-2021 Academic Year. 62 students participated in this study. In the study in which the empirical research method was used, semi-structured, and closed-ended interview technique was used to analyze the design education, and design principles approaches to the students along with demographic questions. For this purpose, a written interview form consisting of 25 questions was sent. The data conveying the design preferences showing the self-report scales obtained with the natural observation method were tabulated with the qualitative research method. As a result of this study, it was observed that the students were introduced to the concept of design for the first time during their university years. It was determined that they had difficulty in understanding the concept of design in the first stage of distance education, and then they showed improvement. Despite this, it was determined that as their experience increased thanks to course applications, and discussions, their perceptions of the course content also improved.
Keywords: Interior Architecture Design Studio; Design Principles; Concept Design; Online Learning; Teaching under Pandemic Period